FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI ORGANIK DI KECAMATAN BATANG ANAI KABUPATEN PADANG PARIAMAN - Widyastuti, Winda; Krestiani, Veronica (Cangkok, 2022)
The purpose of this study was to determine what factors affect the production of organic rice paddy in Batang Anai District, Padang Pariaman Regency. The research method is purposive by taking 41 people as respondents. The method of analysis uses the Cobb-Douglas production function by entering five production inputs such as land area, seeds, fertilizer, organic pesticides and labor to increase organic rice paddy production. The results of the analysis show that the factors that affect the production of lowland rice are land area while land area, seeds, fertilizer, organic pesticides and labor in Batang Anai District, Padang Pariaman Regency.